Appearance and Method of Crowned and Bejeweled Buddha Images Before the 19th Century - Imsamraan, Suchart; Pholprasert, Apichart (Journal of Buddhist Studies Chulalongkorn University, 2022)
The Buddha image is not only a representation of the Lord Buddha, but also a tool for studying artistic eras of different empires. This research article seeks to investigate the relationship and influence among, as well as the physical evolution and religious ideas of, crowned and bejeweled Buddha images before the 19th century in India, Burma, Cambodia, and Thailand. The research found that 1) Indian art in the Pala style is regarded as the model for Crowned and Bejeweled Buddha Images, and has had significant impact on Bagan art (Burma) and Bayon art (Cambodia). Together, these three styles have influenced the arts of Hariphunchai, Srivichai, Lanna, and Lopburi in Thailand. Common beliefs, commerce, religious propagation, and even war helped to spread the popularity of the Crowned and Bejeweled Buddha Images in many areas. The differences in the appearance of the Buddha images depend on varying interpretations, on different combinations between the received art style and the original one, and on the adaptation of the received style to suit the artistic context of that society. 2) The Crowned and Bejeweled Buddha Images in Pala style (India) reflect the beliefs in the Buddha as the supreme being above all, in th e Trikāya, in the Buddha as the King of kings and as the Ādi-Buddha. Those in Bagan art style (Burma) reflect the beliefs in the Buddha as the King of kings, in the Jambupati-sutra, and in the Maitreya Buddha. The ones in Khmer art style (Cambodia) reflect the beliefs in the Buddha as the supreme being above all, in the Trikāya, in the Buddha as the King of kings and as the Adi-Buddha, in the Ratanatriya, and in Phra Bhaisajyaguru Vaitoonprapha (Medicine Buddha).